2022
DOI: 10.1101/2022.12.06.519310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone monoaminylation dynamics are regulated by a single enzyme and promote neural rhythmicity

Abstract: Histone H3 monoaminylations at glutamine(Q) 5 represent an important family of epigenetic markers in neurons that play critical roles in the mediation of permissive gene expression. We previously demonstrated that H3Q5 serotonylation(ser) and dopaminylation(dop) are catalyzed by the Transglutaminase 2 (TGM2) enzyme. Here, we found that TGM2 additionally functions as an “eraser” and “re-writer” of H3 monoaminylations, and identified a new class of this modification, H3Q5 histaminylation(his), which displayed dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(55 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…An additional limitation of the current study is the possibility that our viral dominant negative approach may also impact H3Q5dop in DRN, as both marks are indeed present within this brain region (note that H3Q5his is only very weakly found within DRN (20)), although their relative stoichiometries remain unclear. Presumably, given that the proportion of serotonergic vs. dopaminergic neurons is largely skewed towards that of serotonergic cells in DRN, one might assume that the serotonylation mark would be more dominantly expressed, though this has yet to be tested empirically.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…An additional limitation of the current study is the possibility that our viral dominant negative approach may also impact H3Q5dop in DRN, as both marks are indeed present within this brain region (note that H3Q5his is only very weakly found within DRN (20)), although their relative stoichiometries remain unclear. Presumably, given that the proportion of serotonergic vs. dopaminergic neurons is largely skewed towards that of serotonergic cells in DRN, one might assume that the serotonylation mark would be more dominantly expressed, though this has yet to be tested empirically.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, we hypothesize that these findings may help to explain, at least in part, the delayed efficacy of 5-HT associated ADs in both humans with MDD and preclinical rodent models. Many of our previous findings have suggested that H3 monoaminylation levels are largely dictated by intracellular donor (i.e., monoamine) concentrations (20), but once established in neuronal chromatin, it remains unclear how quickly the marks will be turned over, especially given the relatively slow kinetics of histone turnover observed in both neurons and glia (62). As such, AD treatments may function to increase 5-HT release from serotonergic neurons, thereby reducing intracellular 5-HT concentrations, eventually leading to loss, or restoration, of the mark within these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,26 The enhanced binding affinity between H3Q5ser and WDR5 can be attributed to multiple interactions, such as the cation-π stacking between R4828 of WDR5 and the indole ring of H3Q5ser. 17,27 Although this enhanced binding had no effect on the enzymatic activity of MLL1 for H3K4 methylation, the existence of H3Q5ser could stabilize H3K4me3 from dynamic turnover by profoundly inhibiting the binding and activity of H3K4me3 erasers (such as KDM5B/C and LSD1). 26 To uncover the crosstalk between H3Q5ser and H3K4me3 in colon tumor tissues, we incubated probe 1 and the extracted histone faction of colorectal cancer samples to introduce the biotin tag to serotonylated H3.…”
mentioning
confidence: 99%
“…9,13,14 Recently, we elucidated the biochemical mechanism of another type of intriguing microenvironment-driven histone PTM, i.e., monoaminylation on N-terminal glutamine residue of histone H3 (H3Q5). 15,16,17 The dynamics of this modification, including its installation, removal, and replacement, are regulated by a single enzyme, transglutaminase 2 (TGM2) through a transamination reaction (Fig. 1A).…”
mentioning
confidence: 99%